2005
DOI: 10.1073/pnas.0504981102
|View full text |Cite
|
Sign up to set email alerts
|

Drosophila ATM and ATR checkpoint kinases control partially redundant pathways for telomere maintenance

Abstract: In higher eukaryotes, the ataxia telangiectasia mutated (ATM) and ATM and Rad3-related (ATR) checkpoint kinases play distinct, but partially overlapping, roles in DNA damage response. Yet their interrelated function has not been defined for telomere maintenance. We discover in Drosophila that the two proteins control partially redundant pathways for telomere protection: the loss of ATM leads to the fusion of some telomeres, whereas the loss of both ATM and ATR renders all telomeres susceptible to fusion. The A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
109
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(118 citation statements)
references
References 48 publications
(70 reference statements)
8
109
0
Order By: Relevance
“…dATM mutants also show similar phenotypes associated with ATM patients such as neurodegeneration 10,11 , abnormal telomere protection 12,13 , increased apoptosis and chromosome fragmentation by DSB repair defects 10,11,[13][14][15] . Additionally, dATM participates in silencing the expression of genes adjacent to telomere ends (telomere position effect) 16,17 and in alternative splicing of pre-messenger RNA 18 .…”
mentioning
confidence: 83%
“…dATM mutants also show similar phenotypes associated with ATM patients such as neurodegeneration 10,11 , abnormal telomere protection 12,13 , increased apoptosis and chromosome fragmentation by DSB repair defects 10,11,[13][14][15] . Additionally, dATM participates in silencing the expression of genes adjacent to telomere ends (telomere position effect) 16,17 and in alternative splicing of pre-messenger RNA 18 .…”
mentioning
confidence: 83%
“…Other proteins necessary for capping function are also major components of the DNA damage response (11), as has been found in mammals (34). In particular, members of the Mre11/Rad50/ Nbs (MRN) complex are required to maintain HOAP at the telomere and prevent telomere fusions (35)(36)(37)(38)(39), as are the ATM and ATR kinases (39)(40)(41)(42)(43). The ATM and ATR DNA damage response pathways are partially redundant.…”
Section: Proteins Associated With the Capmentioning
confidence: 99%
“…The ATM and ATR DNA damage response pathways are partially redundant. While loss of ATR does not affect chromosome stability, mutations in both pathways simultaneously results in a greater telomere-fusion mutant phenotype than loss of ATM by itself (40). ATM and MRN, however, appear to work in the same damage response pathway (35).…”
Section: Proteins Associated With the Capmentioning
confidence: 99%
“…In contrast, thanks to the maternal effect that characterizes Drosophila development, null mutations in the mre11, rad50, and nbs genes cause lethality at late larval stages, allowing cytological analysis of dividing neuroblasts in larval brains. Previous studies have shown that mutations in the Drosophila mre11, rad50, nbs, and tefu (ATM) genes cause both telomeric fusions and chromosome breakage and that tefu and mei-41 (ATR) control redundant pathways of telomere protection (Bi et al 2004(Bi et al , 2005Ciapponi et al 2004;Oikemus et al 2004;Silva et al 2004;Song et al 2004). Here, we have explored the role of the Drosophila nbs gene in both telomere protection and the maintenance of chromosome integrity.…”
mentioning
confidence: 99%